The Diversity of Medicinal Herbs of Bogani Ethnic in Bolaang Mongondow, North Sulawesi - Herny E. I. Simbala; Sartje J. Rondonuwu; Edwin De Queljoe (Journal of Tropical Ethnobiology, 2005)
As so far, modern medical system has rapidly progress; however traditional medical system is still prevailing for the most Indonesian people. Bogani ethnic in Residency of Bolaang Mongondow still use traditional medical system. As evidence, traditional medicine ingredients are still used in their daily living. In the case, traditional medicine was used to treat many diseases, from minor diseases (headache, cough, and influenza, to the acute ones such as lung inflamed (113C), liver and tetanus. The research objectives are : (1) to inventory and describe the medicine plant species; (2) to study plant usage as traditional medicine ingredients for many diseases ; (3) as conservation effort of traditional medicine knowledge because most of them not inherited and have limited data, and (4) to collect scientific information regarding the peculiar property of medicine herb where the research information is potential for pharmacology research in order to discover a new medicine ingredient. A rapprochement method for the research is ethno-directed sampling. Following Friedberg (1993) in Purwanto (2002), eihno-directed sampling methods is a data collection of medicine herb material that based on the local knowledge (ethnic) about medicine herbs, treatment technique, ingredients technique and other aspects that related to public health and conducted with ethnoscience approach. Ethnoscience is an approach that enable us to achieve deep understanding and reveal community knowledge system about medicine herb, treatment technique, ingredient technique and other aspect that related to public health. Qualitative and quantitative approach was used as data collection technique. The result showed that there were 56 species of herbs used as traditional medicine material for Bogani ethnics in Bolaang Mongondow; North Sulawesi. The herbs were generally collected from forest area, garden near with settlement area and indeed from cultivation product at yard. There were 34 families of medicine herbs and most of them including family of Euphorbiaceae, Labiatae, Verbenaceae, Araceae, and Asteraceae. Chemical analysis results showed that 8.9 % of medicine herbs contained terpenoid, 42.8 % of medicine herbs contained steroid, 53.5 % contained tannin, 50 % contained flavonoid, 75 % contained alkaloid, and 30 % contained saponin. The analysis indicated that most of herbs positively contained alkaloid as active medicine compound. However the analysis was only as pretest in determining active compound in a medicine herb. There are some medicine herbs classified as endemic should be given priority to be cultivated immediately because their existence are more and more scarce such as Areca vestrana, Musa sp,and Ficus nunahassae. The herbs are almost extinct and need other proper alternative to conserve them.